Editorial - Oniwide, Oyetola (NIU Journal of Management Sciences, 2026)
This edition of NIU Journal of Management Sciences touches on as Marketing Orientation, Consumer Behaviour, Digital Entrepreneurship Orientation, Public Debt Management, Tax Audit Effectiveness and Tax Compliance Behaviour. One of the papers, in this issue, examines how social media exposure and digital entrepreneurship orientation influence youths’ intentions to engage in irregular migration in Plateau State, Nigeria. It therefore, recommends enhanced digital entrepreneurship education and youth-targeted programs to curb irregular migration by creating viable local opportunities. Another paper also reveals that that institutional quality, as measured by the corruption ranking index, has a significant inverse effect on health outcomes in both the long and short run. In contrast, the fiscal freedom index shows a direct, though insignificant, impact on health outcomes in the long run, becoming significant in the short run. The paper therefore, recommends that thorough assessment of debt-financed health projects for sustainability, prioritization of low-interest public loans for health financing, reduction in reliance on external debt for health expenditures, enhancement of transparency and accountability in health spending, and institutional reforms to combat corruption and improve the efficiency of public health investments and its outcome. On the whole, this edition of NIU Management Sciences features many empirical and theoretical based articles which can be of great benefit to every reader.